Implementasi Metode Bahtsul Masail Terhadap Motivasi Belajar PAI - Azizatun Nafiah; Munawir Munawir (Universitas Islam Sultan Agung, 2022)
Learning motivation has a big role in the success of a student. Motivation is seen as a mental impulse that moves and directs human behavior, including learning behavior. Learning outcomes will be optimal if accompanied by the right motivation to learn. In addition to learning motivation, things that can affect the success of the learning process are learning methods. However, this research focuses on the bahtsul masail method which is often used in the learning process in Islamic boarding schools. This study used qualitative research methods. This study aims to obtain general information on social life from the opinion of the informants. The data collection techniques used observation and interview methods. The observation used in this study is a focused type of observation. While the type of interview is a semi-structured interview in-deph-interview category. The results of the study show that this activity is effective for student motivation in PAI learning, this is evidenced by the results of the questionnaire before participating in the Bahtsul Masa'il activity and after participating in the activity, it has increased. Through student indicators, the characteristics of students who are motivated are students who already have these traits seen in the learning process. In addition, the impact of Bahtsul masail activities in PAI learning includes students becoming confident, thinking critically, and practicing problem solving. Keywords: Bahtsul Masail, Implementation, Motivation, Islamic Education.